Concordance between CA-125 and RECIST progression in patients with germline BRCA-mutated platinum-sensitive relapsed ovarian cancer treated in the SOLO2 trial with olaparib as maintenance therapy after response to chemotherapy. (November 2020) - Tjokrowidjaja, Angelina; Lee, Chee K.; Friedlander, Michael; Gebski, Val; Gladieff, Laurence; Ledermann, Jonathan; Penson, Richard; Oza, Amit; Korach, Jacob; Huzarski, Tomasz; Manso, Luis; Pisano, Carmela; et al.
Abstract: Background: Limited evidence exists to support CA-125 as a valid surrogate biomarker for progression in patients with ovarian cancer on maintenance PARP inhibitor (PARPi) therapy. We aimed to assess the concordance between CA-125 and Response Evaluation Criteria in Solid Tumours (RECIST) criteria for progression in patients with BRCA mutations on maintenance PARPi or placebo. Methods: We extracted data on progression as defined by Gynecologic Cancer InterGroup CA-125, investigator- and independent central-assessed RECIST from the SOLO2/ENGOT-ov21(NCT01874353) trial. We excluded those with progression other than by RECIST, progression on date of randomisation, and no repeat CA-125 beyond baseline. We evaluated the concordance between CA-125 progression and RECIST progression, and assessed the negative (NPV) and positive predictive value (PPV). Results: Of 295 randomised patients, 275 (184 olaparib, 91 placebo) were included. 171 patients had investigator-assessed RECIST progression. Of 80 patients with CA-125 progression, 77 had concordant RECIST progression (PPV 96%, 95% confidence interval 90–99%). Of 195 patients without CA-125 progression, 94 had RECIST progression (NPV 52%, 45–59%). Within treatment arms, PPV was similar (olaparib: 95% [84–99%], placebo: 97% [87–100%]) but NPV was lower in patients on placebo (olaparib: 60% [52–68%], placebo: 30% [20–44%]). Of 94 patients with RECIST but without CA-125 progression, 64 (68%) had CA-125 that remained within normal range. We observed similar findings using independent-assessed RECIST. Conclusions: Almost half the patients without CA-125 progression had RECIST progression, and most of these had CA-125 within the normal range. Regular computed tomography imaging should be considered as part of surveillance in patients treated with or without maintenance olaparib rather than relying on CA-125 alone. Highlights: There is poor concordance between CA-125 non-PD and RECIST progression. Half the patients without CA-125 PD had RECIST PD, most had normal CA-125 levels. CT imaging to be considered as part of follow-up rather than relying on CA-125 alone.